Factores macroeconómicos y microeconómicos que influyen en la morosidad de las cajas municipales de ahorro y crédito del Perú: 2010 - 2018 - Chimoy Salazar, Angel Enrique (2021)
The objective of this research is to determine the main macroeconomic and microeconomic factors that have influenced the delinquency of the Municipal Savings and Credit Banks of Peru in the period 2010 - 2018. In order to respond to this problem, a methodology based on the quantitative research approach was followed in order to: explore a treatment to the proposed problem different from that usually used in previous research; describe the behavior and evolution of the variables under study using trend graphs and correlate, using scatter graphs and the Pearson correlation coefficient, the exogenous variables with the delinquency of the CMAC. The results obtained lead to the conclusion that at the macroeconomic level the main factors that have influenced the delinquency of the CMAC in the study period are the economic cycle and unemployment, at the microeconomic level the influence on the delinquency falls on the expansion of the credit, the number of agencies, the risk profile and the degree of solvency.